2013
DOI: 10.1038/onc.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Selective regulation of p38β protein and signaling by integrin-linked kinase mediates bladder cancer cell migration

Abstract: Integrin-linked kinase (ILK) and p38(MAPK) are protein kinases that transduce extracellular signals regulating cell migration and actin cytoskeletal organization. ILK-dependent regulation of p38(MAPK) is critical for mammalian kidney development and in smooth muscle cell migration, however, specific p38 isoforms has not been previously examined in ILK-regulated responses. Signaling by ILK and p38(MAPK) is often dysregulated in bladder cancer, and here we report a strong positive correlation between protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…The ability of the T24-L to form lung metastases may provide a useful tool in understanding the mechanisms driving metastasis in bladder cancer. Consistent with previously published data and our own work, we used this model to implicate several genes that may be involved in bladder cancer metastasis, such as Src, p38, and ILK (31,39,40). However, ATF3-GSN axis may play an alternative role in mediating bladder cancer metastasis and progression independently of the above-mentioned regulators.…”
Section: Discussionsupporting
confidence: 61%
“…The ability of the T24-L to form lung metastases may provide a useful tool in understanding the mechanisms driving metastasis in bladder cancer. Consistent with previously published data and our own work, we used this model to implicate several genes that may be involved in bladder cancer metastasis, such as Src, p38, and ILK (31,39,40). However, ATF3-GSN axis may play an alternative role in mediating bladder cancer metastasis and progression independently of the above-mentioned regulators.…”
Section: Discussionsupporting
confidence: 61%
“…Upon receiving, lines were expanded and frozen aliquots were made in the first 2 months, and fresh aliquots were thawed before the lines reached 6 months in culture. TSU-Pr1 cells (grade 3) were sourced as described previously (30). The identity of all cell lines was authenticated with STR analysis using AmpFLSTR Identifiler Kit from Applied Biosystems at our MHTP Medical Genomics Facility and confirmed that no cross-contamination was present during this study.…”
Section: Cell Culturementioning
confidence: 87%
“…Conversely, p38 inhibitors block the tension-dependent actin remodeling that is characteristic of myofibroblast transformation. In non-fibroblast cell types, p38 regulates actin polymerization and stress fiber formation, suggesting a global role for p38 in transducing mechanical signals into cytoskeletal changes [111-114]. Taken together, p38 and SRF appear to be the primary integrators of signals from several growth factors and mechanically-activated pathways that drive myofibroblast differentiation ( Figure 2 ).…”
Section: The Myofibroblast Differentiation Regulatory Networkmentioning
confidence: 99%